On the Politics of the Classical Economists - Grampp, William D. (Quarterly Journal of Economics, 1948)
"Circumstances give in reality to every political principle its distinguishing color and discriminating effect." Edmund Burke, on the Revolution in France. Introduction, 714. — I. The classical economists' theory of the state and of government, 716. — II. Universal economic, yet hmited political, freedom, 725. — III. Reasons for distrust of popular, and of authoritarian, government, 729. — IV. The paradox of free trade and nationalism, 736. — V. The distribution of power: checks and balances, 739. — VI. The free market as the means to political progress, 742. — Conclusion, 746.